1997
DOI: 10.1079/wps19970016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoids on immune responses in birds

Abstract: Vitamin A is an essential nutrient that has an influence on immune responses in birds. Both low and high vitamin A intakes result in impaired immune responses. Low dietary vitamin A has been shown to cause reduced antibody production, defective T-cell responses and reduced phagocytosis, and decreased resistance to infection by bacterial and viral pathogens and protozoan enteropathogens. Enhanced immune responses can be elicited by high, but not excessive, dosages of vitamin A. Optimum immune responses in growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated a reduced T-cell-mediated immune response in cases of protein malnutrition (Gershwin et al, 1985;Lochmiller et al, 1993). However, dietary deficiencies of other kinds of nutrients, such as amino acids (methionine) and vitamins (e.g., antioxidants), have also been shown to affect the optimal development of the immune system and reduce immune function (Chew, 1996;Friedman and Sklan, 1997;Haq et al, 1996;McWhinney et al, 1989;Tsiagbe et al, 1987). We found that a food supplement of high-calorie paste, enriched with essential micronutrients such as vitamins and minerals, resulted in significantly higher T-cell-mediated immune responses and a tendency to an increased condition index for food-supplemented nestlings (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a reduced T-cell-mediated immune response in cases of protein malnutrition (Gershwin et al, 1985;Lochmiller et al, 1993). However, dietary deficiencies of other kinds of nutrients, such as amino acids (methionine) and vitamins (e.g., antioxidants), have also been shown to affect the optimal development of the immune system and reduce immune function (Chew, 1996;Friedman and Sklan, 1997;Haq et al, 1996;McWhinney et al, 1989;Tsiagbe et al, 1987). We found that a food supplement of high-calorie paste, enriched with essential micronutrients such as vitamins and minerals, resulted in significantly higher T-cell-mediated immune responses and a tendency to an increased condition index for food-supplemented nestlings (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A addition to the diet can prevent inhibition of growth performance in poultry that may be deficient in this vitamin (Yuan et al 2014). Vitamin A levels required to maximize immunocompetence have been displayed to be much higher than that necessary for the feed efficiency and optimum growth (Friedman & Sklan 1997). Dietary vitamin A at a high level of 12,000 IU/kg feed augmented the antibody titer against Newcastle disease virus of hens under heat stress (Lin et al 2002).…”
Section: Vitamin Kmentioning
confidence: 99%
“…Several nutrients are important in the early development of the immune system. Vitamin A is necessary to maximize immuno-competence and for the optimum growth and feed efficiency of poultry (95, 96). Other nutrients which can affect early immune development are linoleic acid, iron, selenium, and some of the B vitamins (97).…”
Section: Effects Of Early Nutrition On the Immune Systemmentioning
confidence: 99%